Cross‐modal Interactions between Color and Texture of Food. Issue 9 (September 2015) - Chylinski, Mathew; Northey, Gavin; Ngo, Liem Viet
ABSTRACT Color has a profound influence on human perception. Not only does it cause changes in physiological or emotional states, it can shape what is perceived in other sensory modalities. However, the body of research on these "cross‐modal" experiences has predominantly examined color's influence on taste and smell. As such, the aim of this study was to identify the cross‐modal influence of color on the sense of touch. In four experiments involving food products, the cross‐modal interaction between color and texture was found to be automatic, unlearned, and a moderating effect on perceived texture. Furthermore, results indicate a person's haptic predisposition, or "need for touch, " influences their sensitivity to these cross‐modal effects. This research builds on current theory involving color, presents a number of areas for future research, and discusses managerial implications of color–texture cross‐modal interactions.